Building blocks play: Model reconstruction, teacher’s guidance and early childhood creativity - M. Marhun (JECCE (Journal of Early Childhood Care and Education), 2020)
Teachers in ECE (Early Childhood Education) should have the knowledge and skills in guiding children when playing blocks, but this is not shared by most PAUD teachers in Indonesia. Therefore, this study develops a block play model that refers to the PKPK model from Hirsch and Dodge with the adjustment of conditions in Indonesia. This research is a research and development (R&D) that seeks to develop, refine (re-construct), test, and validate Masnipal-models that are easy for teachers to use and effectively develop children's creativity. This study begins with testing the PKPK model to a group of subjects to obtain data about the ability of teachers to understand and apply the model. After revisions and improvements, the model of reconstruction results was further tested. Research subjects were PAUD teachers in Cianjur (n = 42) and Bandung (n = 78). Data collection uses observation and peer assessment techniques and data analysis uses descriptive analysis techniques. The novelty of this study is the resulting Masnipal-model that facilitates PAUD teachers in Indonesia in guiding children to develop creativity through block play.